Balancing Conservation and Development: A Policy Framework for Sustainable Forest Management - Sun Wei; Yang Xiang; Zhang Li (Journal of Selvicoltura Asean, 2024)
The interplay between conservation and development poses significant challenges in forest management. Unsustainable practices often lead to biodiversity loss and environmental degradation, highlighting the urgent need for effective policy frameworks that balance these competing interests. Sustainable forest management is essential for preserving ecosystems while supporting economic growth. This research aims to develop a comprehensive policy framework that harmonizes conservation and development goals in forest management. The study seeks to identify strategies that promote sustainable practices, enhance biodiversity, and support local communities' livelihoods. A mixed-methods approach was employed, combining qualitative and quantitative data collection. Case studies from various regions were analyzed to understand existing policies and their impacts on forest management. Stakeholder interviews and surveys were conducted to gather insights on the challenges and opportunities in balancing conservation with development. The findings indicate that successful policy frameworks incorporate multi-stakeholder participation, adaptive management strategies, and comprehensive monitoring systems. The analysis revealed that integrating local knowledge and addressing socio-economic factors are crucial for effective implementation. Case studies demonstrated that successful balance results in improved ecological outcomes and enhanced community well-being. The research underscores the importance of a holistic approach to forest management that aligns conservation and development objectives. By implementing the proposed policy framework, stakeholders can foster sustainable practices that benefit both ecosystems and local communities, ensuring long-term viability and resilience of forest resources.